Flow cytometric predictive scoring systems for common fusions ETV6/RUNX1, BCR/ABL1, TCF3/PBX1 and rearrangements of the KMT2A gene, proposed for the initial cytogenetic approach in cases of B‐acute lymphoblastic leukemia. (7th February 2019) - Tsagarakis, Nikolaos J.; Papadhimitriou, Stefanos I.; Pavlidis, Dimitris; Marinakis, Theodoros; Kostopoulos, Ioannis V.; Stiakaki, Eftichia; Polychronopoulou, Sofia; Paterakis, George
Abstract: Introduction: In B‐acute lymphoblastic leukemia (B‐ALL), the identification of cytogenetic prognostic factors is important for stratifying patients into risk groups and tailoring treatment accordingly. The purpose of this study was to propose flow cytometric (FCM) scoring systems (SSs) for predicting t(12;21)(p13;q22), t(9;22)(q34;q11), t(11q23), and t(1;19)(q23;p13.3) translocations. Methods: We analyzed retrospectively the FCM immunophenotype of 377 patients with B‐ALL with regard to the major cytogenetic findings revealed by interphase fluorescence in situ hybridization (i‐FISH). Comparing descriptive data on the expression of each antigen and performing receiver operating characteristic (ROC) analysis, we identified the most reliable predictive markers for each translocation and sought to establish a specific SS for each translocation, based on specific antibody panels. Results: CD27, CD9, CD66c, CD10, CD25, and CD34 were employed for the prediction of t(12;21), CD25, CD38, CD34, and CD66c for t(9;22), NG2, CD10, CD15, CD34, and CD20 for t(11q23), and CD34, cμ, CD123, and CD66c for t(1;19). The sensitivity and specificity, respectively, of each predictive score were 89.29% and 96.15% for t(12;21), 75.00% and 88.19% for t(9;22), 84.21% and 99.04% for t(11q23), and 85.71% and 92.71% for t(1;19). Conclusion: Four highly specific and significantly sensitive FCM‐obtained SSs are proposed for the prediction of the four major translocations observed in patients with B‐ALL. Prospective evaluation of the proposed SSs could lead to a better targeted cytogenetic investigation and therefore to more cost‐effective laboratory practice.